Synthesis of N-aryl-2,6-diphenyl-2H-pyrazolo[4,3-c]pyridin-7-amines and their photodynamic properties in the human skin melanoma cell line G361 - Razmienė, Beatričė; Vojáčková, Veronika; Řezníčková, Eva; Malina, Lukáš; Dambrauskienė, Vaida; Kubala, Martin; Bajgar, Robert; Kolářová, Hana; Žukauskaitė, Asta; Arbačiauskienė, Eglė; Šačkus, Algirdas; Kryštof, Vladimír (Bioorganic chemistry, 2022)
A small series of N-aryl-2,6-diphenyl-2H-pyrazolo[4,3-c]pyridin-7-amines was synthesized from easily accessible 1-phenyl-1H-pyrazol-3-ol via 7-iodo-2,6-diphenyl-2H-pyrazolo[4,3-c]pyridine and 7-iodo-4-methyl-2,6-diphenyl-2H-pyrazolo[4,3-c]pyridine intermediates and their subsequent use in palladium catalyzed Buchwald-Hartwig cross-coupling reaction with various anilines. Majority of the compounds were not significantly cytotoxic to melanoma G361 cells in the dark up to 10 µM concentration, but their activity could be increased by irradiation with visible blue light (414 nm). The most active compound 10 possessed EC50 values of 3.5, 1.6 and 0.9 µM in cells irradiated with 1, 5 and 10 J/cm2, respectively. The treatment caused generation of reactive oxygen species in cells and extensive DNA damage, documented by the comet assay and by detection of phosphorylated histone H2A.X, followed by apoptotic cell death. Our results suggest that N-aryl-2,6-diphenyl-2H-pyrazolo[4,3-c]pyridin-7-amines could serve as a potential source of photosensitizing compounds with anticancer activities.
Keywords: Cell Survival; fotosenzibilizující látky; Apoptosis; nádory kůže; Pyrazole; Drug Screening Assays, Antitumor; Humans; Cytotoxicity; Skin Neoplasms; Tumor Cells, Cultured; světlo; DNA damage; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; melanom; Photosensitizing Agents; Dose-Response Relationship, Drug; Antineoplastic Agents; Reactive oxygen species; lidé; fotochemoterapie; proliferace buněk; molekulární struktura; Light; nádorové buňky kultivované; Molecular Structure; Melanoma; Photodynamic effect; Buchwald–Hartwig amination; Cell Proliferation; screeningové testy protinádorových léčiv; protinádorové látky; Photochemotherapy; vztah mezi dávkou a účinkem léčiva; viabilita buněk